1994
DOI: 10.2172/10190973
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of ferrocyanide compounds. Ferrocyanide Safety Project, Interim report FY1994

Abstract: The solubility of cs,NiFe(CN),(c) as a function of NaOH and temperature was determined to ascertain whether C@iFe(CN),(c) shows retrograde solubility (Le., decreasing solubility with increasing temperature), which would have bearing on the possible formation of "hot spots" in the tanks and thus the safety of the ferrocyanide tanks. The results show that the aqueous concentrations of Cs in equilibrium with Cs,?NiFe(CN),(c) at 25"C, 60"C, 75"C, and 90°C are similar (within the limits of experimental error), indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…However, strongly deviating degradation mechanisms might have to be considered for battery electrodes under aqueous conditions. In the case of PBA materials for ASIBs, research efforts related to their degradation mainly focused on finding and quantifying dissolved transition-metal cations and hexacyanometallate or cyanide anions in the electrolyte postmortem. Several reasons for the observed instability have been discussed, attributing the loss of active material to the deterioration of the TM–NC–Fe bonds. Although the ligand bindings in Fe­(CN) 6 3/4– themselves are supposed to be stable up to moderately acidic conditions, the interaction of the N-coordinated TM atoms with hydroxide anions is believed to rupture the compound. Naturally, some OH – species will be present in any aqueous electrolytes and might even be specifically adsorbed at cathode materials with operating potentials close to the oxygen evolution reaction (OER), further promoting detrimental side reactions.…”
Section: Introductionmentioning
confidence: 99%
“…However, strongly deviating degradation mechanisms might have to be considered for battery electrodes under aqueous conditions. In the case of PBA materials for ASIBs, research efforts related to their degradation mainly focused on finding and quantifying dissolved transition-metal cations and hexacyanometallate or cyanide anions in the electrolyte postmortem. Several reasons for the observed instability have been discussed, attributing the loss of active material to the deterioration of the TM–NC–Fe bonds. Although the ligand bindings in Fe­(CN) 6 3/4– themselves are supposed to be stable up to moderately acidic conditions, the interaction of the N-coordinated TM atoms with hydroxide anions is believed to rupture the compound. Naturally, some OH – species will be present in any aqueous electrolytes and might even be specifically adsorbed at cathode materials with operating potentials close to the oxygen evolution reaction (OER), further promoting detrimental side reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous testing , on ferrocyanide simulants showed that little dissolution of cesium nickel ferrocyanide occurred when contacted with up to 4 M caustic solution. In these same tests, the sodium nickel ferrocyanide (Na 2 NiFe(CN) 6(s) ) resulted in a measurable hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…Aging studies displayed that sodium nickel ferrocyanide reacted with free hydroxide to form nickel hydroxide and ammonia under tank conditions and, when driven to completion, increased the cesium content in solution . Ferrocyanide simulant studies, however, concluded that cesium nickel ferrocyanide was a stable compound in up to 4 M sodium hydroxide. , No studies were done, however, on the stability of the cesium nickel ferrocyanide in aged real waste and under tank conditions.…”
Section: Introductionmentioning
confidence: 99%